2005
DOI: 10.1111/j.1600-6143.2005.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Living Kidney Donors: Clinical Characteristics and Outcomes in the Era of Laparoscopic Donor Nephrectomy

Abstract: Acceptance of obese individuals as living kidney donors is controversial related to possible increased risk for surgical complications and concern that obesity may contribute to long-term renal disease. We retrospectively examined 553 consecutive hand-assisted laparoscopic living kidney donations between October 1, 1999 and April 1, 2003. We stratified donors into quartiles by baseline body mass index (BMI) assessing perioperative complications and 6-12 months post-donation metabolic and renal function. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 24 publications
6
111
2
3
Order By: Relevance
“…When proteinuria and albuminuria were evaluated, there was a trend toward higher levels of total urine protein and albumin in donors who were obese at donation, and the incidence of abnormal proteinuria was significantly increased in the obese; however, the incidence of abnormal albuminuria was not significantly different between the two groups. These findings corroborate other reports demonstrating relative preservation of renal function in obese donors on short-term follow-up (19,20,22) but differ from several large-scale population studies that examined the impact of obesity on renal function. For example, a recent study which examined Ͼ350,000 adult patients in the Kaiser-Permanente system in California found that obese patients had a significantly increased incidence of ESRD compared with normalweight control subjects.…”
Section: Discussionsupporting
confidence: 80%
“…When proteinuria and albuminuria were evaluated, there was a trend toward higher levels of total urine protein and albumin in donors who were obese at donation, and the incidence of abnormal proteinuria was significantly increased in the obese; however, the incidence of abnormal albuminuria was not significantly different between the two groups. These findings corroborate other reports demonstrating relative preservation of renal function in obese donors on short-term follow-up (19,20,22) but differ from several large-scale population studies that examined the impact of obesity on renal function. For example, a recent study which examined Ͼ350,000 adult patients in the Kaiser-Permanente system in California found that obese patients had a significantly increased incidence of ESRD compared with normalweight control subjects.…”
Section: Discussionsupporting
confidence: 80%
“…These perioperative findings are consistent with results from other authors who evaluated obese donors. 5 Surgical mortality and major morbidity after nephrectomy was not associated with obesity in the present and previous work. 7 Several studies have shown that renal parameters, including GFR and proteinuria, are significantly affected after unilateral nephrectomy, with 40% reduction in GFR.…”
Section: Discussionsupporting
confidence: 56%
“…[5][6][7][8][9] United Kingdom guidelines support the practice of using otherwise healthy overweight and moderately obese donors (body mass index [BMI] = 25 to 35 kg/m 2 ). Guidelines have been modified recently for very obese status (BMI ≥ 35 kg/m 2 ) from being an absolute contraindication, and very obese potential donors are "discouraged" but not prevented from donating.…”
Section: Safety Of Nephrectomy In Morbidly Obese Donorsmentioning
confidence: 99%
“…Although consensus statements encourage weight loss and healthy lifestyle education in obese donors (78), there is no evidence that this lowers obesity risks in living donors. In one prospective study of living donors, there was no change in body mas index among overweight, obese, or extremely obese donors at 1 yr after donation (5).…”
Section: Eventsmentioning
confidence: 99%